Structure Formation in an Ionic Liquid Wetting Layer: A Combined STM, IRAS, DFT and MD Study of [C2C1Im][OTf] on Au(111) - Bühlmeyer, Hanna; Hauner, Jonas; Eschenbacher, Roman; Steffen, Julien; Trzeciak, Simon; Taccardi, Nicola; Görling, Andreas; Zahn, Dirk; Wasserscheid, Peter; Libuda, Jörg (Chemistry - A European Journal, 2023)
In a solid catalyst with ionic liquid layer (SCILL), ionic liquid (IL) coatings are used to improve the selectivity of noble metal catalysts. To understand the origins of this selectivity control, we performed model studies by surface science methods in ultrahigh vacuum (UHV). We investigated the growth and thermal stability of ultrathin IL films by infrared reflection absorption spectroscopy (IRAS). We combined these experiments with scanning tunneling microscopy (STM) to obtain information on the orientation of the ions, the interactions with the surface, the intermolecular interactions, and the structure formation. Additionally, we performed DFT calculations and molecular dynamics (MD) simulations to interpret the experimental data. We studied the IL 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C2C1Im][OTf] on Au(111) surfaces. We observe a weakly bound multilayer of [C2C1Im][OTf], which is stable up to 390 K, while the monolayer desorbs at ∼450 K. [C2C1Im][OTf] preferentially adsorbs at the step edges and elbows of the herringbone reconstruction of Au(111). The anion adsorbs via the SO3 group with the molecular axis perpendicular to the surface. At low coverage, the [C2C1Im][OTf] crystallizes in a glass-like 2D phase with short-range order. At higher coverage, we observe a phase transition to a 6-membered ring structure with long-range order.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Au(111); SCILL; infrared reflection absorption spectroscopy; ionic liquids; scanning tunneling microscopy